Sítio arqueológico Pedra do Sol, Município de São Luiz-Roraima : levantamento sobre o estado de conservação e geodiversidade - Souza, Fabrícia Oliveira de (2021)
The present work aimed to study the conservation status and geodiversity of the Pedra do Sol Archaeological site, located in the municipality of São Luiz, state of Roraima, Brazil. The archaeological records are characterized exclusively by engravings housed in the granite rocky support that formed it, as well as in the rolled blocks, slabs and boulders located around it. The methodology was based on the elaboration of maps of land use and occupation of the years 1990, 2005 and 2020, geological and geomorphological of the region in which the site is located, carrying out field expeditions to describe the geological aspects with collections of samples for macroscopic descriptions and petrographic analysis, observation of geomorphological aspects and identification of agents of degradation of rock records using the rock art stability index (RASI), for the elaboration of a conservation diagnosis. Based on modal analysis in petrographic microscopy, the rocks described in the study area were classified as monzogranites composed essentially of quartz, plagioclase, potassium feldspar and micas (biotite and muscovite). From the in situ and laboratory analyses, the main chemical changes generated mainly by the action of water that transformed minerals such as potassium feldspar and plagioclase into clay minerals and biotite into chlorite, physical caused by temperature variations, biological produced by insects such as termites, small animals, cattle and plant roots and human impacts, especially the fires for the renovation of pastures, which are affecting the rock art panels, with that the conservation status of the panels was classified as critical. Through this diagnosis, we sought to propose actions that can help in the conservation, protection and adequate management of this fragile cultural resource.